Dexamethasone does not affect endolymphatic hydrops (EH) in patients with Meniere's disease within 24 h, and intratympanic administration of gadolinium plus dexamethasone simplifies high-quality imaging of EH using a novel protocol of 7 min - Jing Zou; Zikai Zhao; Hongbin Li; Guoping Zhang; Qing Zhang; Jianping Lu; Ilmari Pyykkö (Journal of Otology)
Background: Intratympanic administration of gadolinium chelate allows for a better visualization of endolymphatic hydrops (EH) using MRI than intravenous injection and was recently further improved to facilitate high-quality imaging of EH in 7 min. The aim of the present study was to simplify the intratympanic administration protocol by mixing gadolinium chelate with therapeutic dexamethasone and to evaluate the effects of this mixture on the visualization of EH in MRI. Materials and methods: In an in vitro study, the potential impact of gadolinium-diethylenetriamine pentaacetic acid (Gd-DTPA) on the stability of dexamethasone was evaluated by analyzing dynamic changes in dexamethasone with high-performance liquid chromatography (HPLC) after mixing with Gd-DTPA. Ten patients with definite Meniere's disease (MD) were recruited to study the potential interference of dexamethasone on MRI visualization of EH, and 49 patients with MD were recruited to evaluate the effect of intratympanic injection of Gd-DTPA mixed with dexamethasone on MRI of EH using a 3T MR machine and a novel heavily T2-weighted 3-dimensional fluid-attenuated inversion recovery reconstructed using a magnitude plus zero-filled interpolation (hT2FLAIR-MZFI) sequence. Results: The retention times and peak area of dexamethasone in HPLC were not modified by the addition of Gd-DTPA. EH grading in the cochlea and vestibule was not influenced in any ear by intratympanic injection of dexamethasone. Excellent inner ear images were obtained from all patients, and EHs with various grades were displayed. There were significant correlations between diagnosis and cochlear EH (p < 0.01, Spearman's Rho), between diagnosis and vestibular EH (p < 0.01, Spearman's Rho), and between cochlear and vestibular EH (p < 0.01, Spearman's Rho). The distribution of Gd-DTPA plus dexamethasone negatively correlated with the grade of vestibular EH. Injury of the endolymph-perilymph barrier was detected in one cochlea and three vestibules of 59 inner ears with MD. Conclusions: Intratympanic administration of Gd-DTPA plus dexamethasone yielded high-quality MRI images of EH in patients with MD using a novel 7-min protocol and simplified the clinical application. Intratympanic administration of Gd-DTPA plus dexamethasone might be used to test its therapeutic effect in future work. Level of evidence: 3.